(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The series connected DVR will inject three-phase compensating voltages through the three phase injection transformer or three single-phase injection transformers with the main supply. The filtered VSI output voltage is boosted the desired level with the injection transformer.The transformer also isolates the DVR circuit from the distribution system. The capacity of the voltage source inverter (VSI) and the values for the link filter connected between the injection transformer and the inverter play a crucial in the design of the DVR. In this research project, new Dynamic Voltage Restorer (DVR) topology has been proposed. The capacity of the voltage source inverter (VSI) and values of the link filter is small that will improve the compensation capabilities for voltage harmonic, swell and voltage sagmitigation under various fault conditions. The new RLC filter is able to eliminate the switching harmonics. The capacity of the dc supply voltage is reduced when the value of inductance is small. The new DVR topology has high efficiency and the ability to improve the quality of voltage. An outline architecture of the RLC filter parameters for the specific model has been presented. The new DVR with proposed controlled Dynamic Voltage Restorer topology is modelled and simulated using the MATLAB. The control scheme has good control dynamics with minimum transient current overshoot.